New trends and topic changes of JBEM 2007–2019: a bibliometric review - Lei, Xintu; Xu, Qingyuan (Journal of Business Economics and Management, 2021)
The Journal of Business Economics and Management (JBEM) has been very active in the field of economics and management science and brought many influential outputs in the last decades. This paper investigated the current status of publications and citations from JBEM and explored the hot topics and new trends represented by most used keywords extracted from the published articles from 2007 to 2019. The data were analyzed and mapped with respect to the most cited literature, most prolific authors, and publication records categorized by authors, institutions and countries. The analysis revealed that papers published each year by the JBEM is relatively stable and published papers has an expected citation number 7.68 times. The difference in frequency of keywords in different stages give us informative clue for future studies. The emerging topics include “SMEs” “Information” “framework” “perspective”, hence the likely focus of JBEM to consider submission of papers centered on these topics, the comparison of keywords between JBEM and Hot Papers & Highly Cited Papers was made as well. Some new trends, for example, information science combining with management science are new hot topics.